Revealing patterns in the aggregation and deposition kinetics of the solid phase in drilling wastewater - Shestopalov, Oleksii; Rykusova, Nadegda; Hetta, Oksana; Ananieva, Valeriia; Chynchyk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
We have investigated the influence of the concentration of the solid phase of drilling wastewater on a change in the sedimentation rate of the solid phase at aggregation when applying a physical-chemical method of water purification using flocculants and coagulants. This is important because a change in the concentration of the solid phase in wastewater is an uncontrolled process during reagent-based purification and it significantly affects the aggregation mechanism, as well as the kinetics of a solid phase sedimentation. The study was performed using the model wastewater prepared by diluting the used drilling mud with tap water. It was found that the use of flocculants without coagulants is not effective and does not lead to aggregation. It was established that the optimum dose of the coagulant aluminum sulfate that is capable of disrupting the stability of the disperse system of drilling wastewater is 65 mg/g, while increasing the dosage of coagulant has no effect on the rate of flake deposition. Among the flocculants, the most active one is the anionic flocculant A-19. Sludge thickening results in the destruction of floccules; in 9 minutes, the floccule deposition rate is reduced two-fold. Increasing the concentration of a flocculant from 0.8 mg/g to 1.6 mg/g leads to an increase in the deposition rate of the solid phase by 2‒2.5 times. It is shown that the solid phase concentration affects the sedimentation rate of floccules; optimum conditions for aggregation are observed at a concentration of 4‒6 g/l. Mechanical impacts on aggregates exert a destructive effect depending on the concentration of the solid phase. It has been established that changes in the dispersed system can be observed based on a change in pH, which varies depending on the concentration of the solid phase in drilling wastewater. Increasing the concentration of the solid phase from 1 to 10 g/l leads to the change in pH from 7.2 to 8.3; the introduction of coagulant reduces pH, while the subsequent destruction of aggregates leads to an increase in pH. The data obtained in the course of our research, as well as the proposed procedure, could be used in order to select the optimal dosages of reagents during drilling wastewater treatment